2017
DOI: 10.9734/csji/2017/32570
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Biodegradation of Nanocellulose Reinforced Polyvinyl Alcohol Blend Films in Bioenvironmental Media

Abstract: Solution casting method was used to prepare nanocellulose reinforced polyvinyl alcohol (PVOH) from Oil palm empty fruit bunches. Different environmental test were used to investigate the biodegradability of the composite in soil and compost as well as in water and acidic solution. The morphology of the composite was investigated by scanning electron microscopy. The composite film with nanocellulose and without nanocellulose were compared, nanocellulose modified PVOH film showed more highly degradable by soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition to the improved workability, flexibility, and barrier properties of the CNC films using additives, their biodegradability preservation is essential to make them suitable to be used in different final applications. It has been reported that the addition of nanocellulose in several composites or films with polyvinyl alcohol, starch, natural and nitrile rubber, , and PBAT increases its biodegradability. The additives used are natural, and therefore, they are supposed to be biodegradable.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the improved workability, flexibility, and barrier properties of the CNC films using additives, their biodegradability preservation is essential to make them suitable to be used in different final applications. It has been reported that the addition of nanocellulose in several composites or films with polyvinyl alcohol, starch, natural and nitrile rubber, , and PBAT increases its biodegradability. The additives used are natural, and therefore, they are supposed to be biodegradable.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies also reported the biodegradable properties of NC. , For example, the addition of CNC into a starch and glycerol film could increase the biodegradability of the film, whereas CNC immobilized bacteriocin could cause a moderate decrease of biodegradability due to antibacterial activity of bacteriocin . In another study, it has been shown that the addition of NC considerably increased the biodegradability of poly­(vinyl alcohol)/NC composite . In the case of CNF, it has been shown that the addition of pristine and modified CNF (acetylated) could decrease the fungal degradation ability of thermoplastic starch film.…”
Section: Introductionmentioning
confidence: 95%
“…[ 16 ] Cellulose nanocrystals (CNC) are produced from the acid hydrolysis of cellulose and its potential has been widely researched especially as reinforcement fillers in hydrophilic polymers. [ 17–20 ] From previous studies, it had been proven that the compatibility and bonding potential between the matrix and reinforcing fillers is the key factor in altering the properties of a composite. [ 21,22 ] Since both nanocellulose and PVOH are polar polymers, their compatibility were excellent and major improvements had been shown.…”
Section: Introductionmentioning
confidence: 99%